HOMEWORK IN ELEMENTARY SCHOOLS - Karimova Dilzodaxon Lazizovna (Scientific Impulse, 2023)
This article explains the benefits and difficulties of doing homework for elementary school pupils and some researchers’ opinions about the period of doing homework.